Acalypha pendula - Edward F. Gilman (EDIS)
This ground-hugging, fine-textured relative of the more common chenille plant grows no more than several inches tall. In the full sun it forms a thick canopy of tiny, serrated leaves no more than 3/4 inches long by 1/2 inches wide (Figure 1). Bright red, fussy flowers stand erect above the foliage like soldiers in a field. This document is Fact Sheet FPS-005, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and and Agricultural Sciences, University of Florida. Publication date: October 1999; reviewed October 2003.